Economic substance and legal form: Modern approaches to contradictions’ analysis - A. A . Aksent’ev (Учёт. Анализ. Аудит, 2022)
Economic substance and legal form are important factors that determine the nature of the information reflected in the reporting. The specialists apply the principle of “substance over form” in each of the information systems in its own way for financial and tax accounting. This makes it possible to fully satisfy users in terms of the data necessary both for making economic decisions and for conducting fiscal procedures. The objects of the study are the financial and tax areas, as well as their respective approaches to the analysis of contradictions between substance and form. The author presents key aspects that reflect the modern views of the scientific community, as well as describes the controversial issues regarding the application of this principality. The conclusions of many experts allow us to assert that there are still disagreements on this subject. They determine the relevance of studying the concepts that explain the interaction of substance and form in both financial and tax accounting. The results of the work are intended for specialists in the field of accounting, auditing and tax law.